1997
DOI: 10.1021/jp962581d
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Formation of Close-Packed Phenyl Layers on Si(111)

Abstract: 4-NO2 and 4-Br benzenediazonium salts have been electrochemically reduced on H-terminated Si(111) electrodes. Electrochemical measurements evidence that the reaction results in a robust modification of Si(111) surfaces. XPS shows that organic films are monolayer thick and that covalent ≡SiAr bonding occurs, with no oxide at the interface. In the case of the Br salt, quantitative RBS measurements suggest that layers are (2×1) close-packed and assess their stability against several rinsing procedures including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
280
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 334 publications
(292 citation statements)
references
References 29 publications
9
280
0
1
Order By: Relevance
“…This adventitious nitrogen signal was also observed by other groups. 6,7,17,18 Generally, our findings from XPS are similar to those of refs 6 and 7 where grafting also occurred on Si(111). For the methoxybenzene process, the C1s intensity was much less, indicating a considerably smaller adsorbate layer thickness.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…This adventitious nitrogen signal was also observed by other groups. 6,7,17,18 Generally, our findings from XPS are similar to those of refs 6 and 7 where grafting also occurred on Si(111). For the methoxybenzene process, the C1s intensity was much less, indicating a considerably smaller adsorbate layer thickness.…”
Section: Resultssupporting
confidence: 89%
“…3 For the elemental semiconductor silicon, organic surface functionalization by wet processes was demonstrated by alkylation 4,5 and by electrochemical grafting of aryl groups. 6,7,8 The latter process as developed in refs 6 and 7 is illustrated in Figure 1. By electron injection into a solution of diazonium salt BF 4 N 2 -C 6 H 4 -X, intermediate aryl radicals •C 6 H 4 -X are formed (Figure 1a).…”
Section: Introductionmentioning
confidence: 98%
“…193 When the reduction was performed in aqueous electrolytes containing diluted sulfuric acid combined with 2% hydrofluoric acid, the reaction gave no detectable high-binding energy shifts in the Si 2p XPS spectra (even at low take off angles, 5-101) indicating the absence of SiO x species. 107 Allongue and co-workers, on the basis of Rutherford backscattering, STM imaging, angle resolved XPS, capacitance measurements, and from the measured charged passed during the grafting process, 194 concluded that no appreciable multilayer formation occurred 107,117,191 under the cathodic conditions used. A reaction scheme for the electrochemical reduction of diazonium salts on hydride silicon was also proposed: 191 X-Ar-N + RN + e À -X-Ar + N 2 (4)…”
Section: Lewis Acid-catalyzed Hydrosilylation Reactionsmentioning
confidence: 99%
“…Strategies to achieve potentially useful molecular-level control over the electrical properties of Si surfaces must therefore ensure that the resulting low S persists in air for extended time periods. Crystalline Si has been functionalized previously at atmospheric pressure with organic layers through the use of alkyl Grignard and alkyl lithium reagents, 6 alkenes, [7][8][9] and phenyldiazonium salts, 10 while the reaction chemistry of porous Si has been developed yet further to include use of alkynes 11,12 and organohalides. 13 The electrochemical properties of some of these surfaces have been reported, 14,15 but to date there appears to be no information on the electrical properties of such systems.…”
Section: ͓S0003-6951͑00͒01739-3͔mentioning
confidence: 99%